Drug utilization pattern in dermatology outpatient department at a tertiary care hospital in Navi Mumbai - Patil, Arun; Dighe, Darshana; Kolte, Shrikrishna; Jadhav, Pradeep R.; Deshmukh, Y. A. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Skin diseases are common and cause a huge disease burden globally. Different class of drugs and combinational products are available in dermatology for treatment. Periodic prescription analysis in the form of drug utilization study can improve the quality of prescription and curb the menace of irrational prescribing. Aim and objective of the study were to study the prescribing pattern and drug utilization trends in Dermatology outpatient department at a tertiary care hospital in Navi Mumbai. Methods: A cross-sectional, observational study was conducted over a period of three months in dermatology department of a tertiary care teaching hospital, Navi-Mumbai. A total of 102 adult patients visiting dermatology OPD were included and their prescriptions were analyzed with WHO prescribing indicators and additional indices. Results: Analysis showed that the average number of drugs per prescription was 3.27. Percentage of drugs prescribed by generic name was 31.1%. Percentage of drugs prescribed from National Essential drug list (NEDL) was 44.2%. The commonest prescribed drugs were antihistaminics followed by antifungals. Oral tablets were the commonest prescribed dosage form. Conclusions: Antihistaminics and antifungals dominated the prescribing pattern in this study with restraint on polypharmacy, but showed ample scope for improvement to prescribe generic and selection of essential drugs.